ANÁLISE DAS ANOTAÇÕES DO ENFERMEIRO EM UMA UNIDADE DE TERAPIA INTENSIVA - MARIA CRISTINA FERREIRA FONTES; ISABEL AMÉLIA COSTA MENDES; MIYEKO HAYASHIDA; MARIA CELIA BARCELLOS DALRI (Universidade Federal do Ceará, 2006)
This is a retrospective study of the nurse's notes taken when patients are admitted to the Intensive Therapy Unit of a teaching hospital in the state of Paraná. As secondary database, we used the files of patients hospitalized in the second semester of 2002. Among the 241 collected files, 187 (77.6%) contained the printed version of the nurse's notes. Most notes were identified by the nurse's rubrics (50.3%) or name (38.0%). From the qualitative analysis of the 187 nurse's notes, we extracted 515 contents, recorded with objective writing (56.6%), readable and clear handwriting (56.6%), correct abbreviations (67.0%), free from errors (95.2%) and shortenings (50.7%). Although most analyzed contents were classified as adequate, we observed flaws in some of the examined characteristics. Such features suggest the need for reflection and further investigation.